Heritage Asset Rumah Saoraja: Analisis Nilai Ekonomi, Nilai Budaya, dan Implikasinya terhadap Akuntansi Budaya - Rahmat Hidayat; A.M. Rahmat Ramadhani Al Kautsar .M; Riri Sundari; Amelia Saputri; Reski Amelia; Muhammad Yamin (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study analyzes the cultural values of Rumah Saorajana in Lemoape Village and their implications for cultural accounting from a heritage asset perspective. A qualitative approach with an interpretive paradigm and phenomenological method was employed. Data were collected through observation, in-depth interviews, documentation, and literature review, and analyzed using the Miles, Huberman, and Saldaña interactive analysis model. The findings indicate that Rumah Saorajana fulfills the characteristics of a heritage asset by embodying historical, social, educational, and cultural values reflected in the Bugis principles of siri', sipakatau, sipakalebbi, and sipakainge. These values represent intangible cultural values that generate sustainable social and cultural benefits despite providing no direct economic returns. The study also identifies the absence of formal inventory, administrative recording, and disclosure systems for cultural assets. The findings contribute to the development of cultural accounting by integrating local cultural values into public asset management while promoting transparency and accountability in heritage conservation.